(untitled) (Italian Journal of Public Health, 2009)
Background: The exceptional changes in the Romanian society after 1989 have strongly influenced the reforms of the health system. Methods: Several tools were used for this health policy review: finding the evidence to prove that there are important public health problems in Romania, as well as reviewing the existing legislation and policy papers related to health system, stakeholder analysis, meetings and working groups with key players from the health sector. Results: Health indicators for Romania are some of the poorest in the WHO European region, not only at EU level. A mix of specific indicators for developed countries (e.g. high mortality by cardiovascular diseases, increasing incidence of cancer) and specific indicators for developing countries (e.g. re-emergence of some communicable diseases, like TB) can be noticed. Unfavourable comparisons also exist for the indicators describing the performance of the health system: poor access to basic health services especially in rural area, inadequate human resources management, lack of integration of the health services in order to assure the continuity of care, poor health information management, and reduced intersectoral cooperation. Six major intervention areas have been identified by the Presidential Health Commission set up in 2008, in order to address the dysfunctions of the health system: Health system financing, Health system organization, Drug policy, Primary care, Hospital services and Human resources. In order to address them, 29 specific recommendations were made. Conclusions: If the declared intentions of the new minister of health are implemented in line with the proposed presidential strategy, then coherency might finally have a chance to drive the process forward.